Respostas

2013-11-25T13:08:53-02:00
A-       x+y=3                             
           x-y=1                                                                                   
1   1   3
1   -1   1

1*(-1)+1*1 = -1-1 = -2
O determinante é -2, vamos calcular x

3   1
1   -1
3* -1 -1 *1 = -3-1 = -4/-2 = x vale 2, vamos calcular y

1   3
1   1
1*1 -3*1 = 1-3 = -2/-2 = y vale 1


B-  x+y+z=10
     x-y+z=4
    x-y-z=0

1   1      1
1   -1   1
1   -1   -1

1-(-1) -
(-1) - (-1) = 4
O determinante é 4, vamos calcular x
10 +0 +(-4) = 6-(-4)-(-10)-0 = 20/4 =  x vale 5, vamos calcular y

(-4)+10+0 = 6-(-10)-0-4 = 12/4 = y = 3, vamos calcular z

0+4+(-10) = -6-0-(-4)-(-10) = 8/4 = 2 z vale2
1 5 1